A patternable anti-"coffee ring effect" hydrogel colorimetric test paper and its preparation method and application

By using the patterned anti-"coffee ring effect" hydrogel colorimetric detection test strip on paper-based colorimetric sensing test strips, the problem of uneven display of colorimetric signals is solved, higher detection sensitivity and specificity are achieved, and suitable for use in different temperatures.

CN115389490BActive Publication Date: 2025-04-22SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210928052.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-03
Publication Date
2025-04-22
Estimated Expiration
2042-08-03

AI Technical Summary

Technical Problem

The existing paper-based colorimetric sensing test papers have the problem of uneven display of colorimetric signals, which leads to a decrease in detection sensitivity and specificity, and it is difficult to adapt to different temperature usage intervals.

Method used

The preparation method of patterned anti-coffee ring effect hydrogel colorimetric detection test paper is used to prepare a hydrophilic and patterned semi-closed paper substrate through screen printing and UV photocuring technology, and hydrogel is prepared using materials such as acrylamide and gelatin prepolymerization, and load detection reagents to form a uniform colorimetric signal.

Benefits of technology

It realizes uniform display of colorimetric signals, improves detection sensitivity and specificity, and can adapt to the use of different temperature ranges, and has the potential for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115389490B_ABST
    Figure CN115389490B_ABST
Patent Text Reader

Abstract

The present invention discloses a patternable anti-"coffee ring effect" hydrogel colorimetric test paper and a preparation method and application thereof. In the present invention, two hydrogel prepolymer systems are first designed for different detection systems, and three detection reagent systems are prepared for different analytes. The detection reagent is then loaded into the hydrogel three-dimensional network by a one-pot method, and further combined with a paper-based fiber array to obtain a colorimetric detection hydrogel test paper that can be used to detect divalent copper ions, divalent iron ions or glucose. The colorimetric test paper prepared in the present invention solves the problem of uneven display of colorimetric signals of conventional paper test papers. It can evenly display colorimetric signals and has a wide adjustable operating temperature range, which is conducive to industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of detection, and particularly relates to a patternable anti-"coffee ring effect" hydrogel colorimetric detection test paper and a preparation method and application thereof. Background Art

[0002] Paper-based colorimetric sensor strips are widely used in the field of rapid diagnosis due to their low cost, easy preparation, convenience and portability. Although research on paper test strips in terms of manufacturing process and detection technology has made rapid progress in recent years, the common problem of uneven display of colorimetric signals has been prevalent since the invention of paper-based detection, directly affecting the sensitivity and specificity of detection and restricting its further development.

[0003] The uneven color display of paper test strips is caused by the uncontrollable flow, spreading and evaporation behavior of biochemical fluids in paper-based fiber arrays, which is prominently manifested as the "coffee ring effect" produced when the two interact with each other. So far, the literature has reported a variety of solutions, from regulating the added biochemical fluid droplets, designing the suitability of paper base materials, applying external forces to suppress capillary forces and Marangoni effects, etc., to ultimately achieve uniform display of paper test strip colorimetric signals. However, the above methods are limited by the properties of the solute particles themselves, and the operation process is cumbersome and difficult to control. They are often limited to laboratories and difficult to apply industrially.

[0004] For example, the paper (Wu Jing. Preparation of paper-based detection chip and application of colorimetric detection method [D]. South China University of Technology.) discloses a preparation of a paper-based detection chip and its colorimetric detection method, which rapidly prepares patterned paper-based test paper through UV curing-screen printing method, and the result analysis method based on light transmission can be used for quantitative analysis of copper, iron and nickel ions in water. However, there is a problem of uneven colorimetric signal of the paper test paper, and it cannot adapt to different temperature usage ranges.

[0005] Therefore, providing a paper-based colorimetric test paper that can overcome the "coffee ring effect" and can be adapted to use in different temperature ranges has broad application prospects. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a patternable anti-"coffee ring effect" hydrogel colorimetric test paper.

[0007] Another object of the present invention is to provide a patternable anti-"coffee ring effect" hydrogel colorimetric test paper prepared by the method.

[0008] Another object of the present invention is to provide an application of the patternable anti-"coffee ring effect" hydrogel colorimetric test paper.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A method for preparing a patternable anti-"coffee ring effect" hydrogel colorimetric test paper comprises the following steps:

[0011] (1) Preparation of hydrophilic and hydrophobic patterned semi-enclosed paper substrate:

[0012] A hydrophilic pattern area with a hydrophilic-hydrophobic boundary and a closed bottom is printed on paper by screen printing and ink, and a patterned hydrophilic detection area is obtained after UV curing;

[0013] (2) Preparation of hydrogel prepolymer solution

[0014] ① Acrylamide prepolymer solution: dissolve acrylamide in glycerol aqueous solution, add cross-linking agent N,N-methylenebisacrylamide (MBA), stir until clear and transparent to obtain acrylamide prepolymer solution;

[0015] ② Gelatin prepolymer solution: dissolve gelatin in water to obtain gelatin prepolymer solution;

[0016] (3) Preparation of detection reagents

[0017] ③ Preparation of copper ion detection reagent: dissolve hydroxylamine hydrochloride in glycerol aqueous solution to obtain hydroxylamine hydrochloride glycerol aqueous solution (detection reagent 1); dissolve 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline in methanol to prepare a saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution (detection reagent 2);

[0018] ④ Preparation of divalent iron ion detection reagent: dissolve 1,10-phenanthroline in methanol aqueous solution to obtain a methanol aqueous solution of 1,10-phenanthroline (detection reagent 3);

[0019] ⑤ Preparation of glucose detection reagent: dissolve glucose oxidase and horseradish peroxidase in hydrochloric acid aqueous solution to obtain a mixed aqueous solution (detection reagent 4); dissolve 3,3',5,5'-tetramethylbenzidine (TMB) in water to obtain a 3,3',5,5'-tetramethylbenzidine aqueous solution (detection reagent 5);

[0020] (4) Preparation of paper-based colorimetric detection hydrogel

[0021] ⑥ Copper ion colorimetric detection hydrogel test paper: the acrylamide prepolymer solution obtained in step ①, the hydroxylamine hydrochloride glycerol aqueous solution (detection reagent 1) obtained in step ③ and the saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution (detection reagent 2) are mixed evenly, and then the initiator solution is added and shaken to mix evenly to obtain a gel mixture I; the gel mixture I is then added dropwise to the patterned hydrophilic detection area obtained in step (1), and then transferred to a vacuum environment for reaction to obtain a copper ion colorimetric detection hydrogel test paper, that is, the patternable anti-"coffee ring effect" hydrogel colorimetric detection test paper;

[0022] ⑦ Hydrogel test paper for colorimetric detection of divalent iron ions: the acrylamide prepolymer solution obtained in step ① and the methanol aqueous solution of 1,10-phenanthroline obtained in step ④ (detection reagent 3) are mixed evenly, and then the initiator solution is added and shaken to mix evenly to obtain a gel mixture II; the gel mixture II is then added dropwise to the patterned hydrophilic detection area obtained in step (1), and then transferred to a vacuum environment for reaction to obtain a hydrogel test paper for colorimetric detection of divalent iron ions, that is, the patternable anti-"coffee ring effect" hydrogel colorimetric detection test paper;

[0023] ⑧ Glucose colorimetric detection hydrogel test paper: the gelatin prepolymer solution obtained in step ②, the mixed aqueous solution obtained in step ⑤ (detection reagent 4) and the 3,3',5,5'-tetramethylbenzidine aqueous solution (detection reagent 5) are mixed evenly, and then the initiator solution is added and shaken to mix evenly to obtain a gel mixture III; the gel mixture III is then added dropwise to the patterned hydrophilic detection area obtained in step (1), and then transferred to a closed environment at room temperature for reaction to obtain a glucose colorimetric detection hydrogel test paper, that is, the patternable anti-"coffee ring effect" hydrogel colorimetric detection test paper.

[0024] The pattern described in step (1) can be designed according to actual needs and can be a customized pattern.

[0025] The size and shape of the patterned hydrophilic detection area described in step (1) can be set according to actual needs; preferably, the patterned hydrophilic detection area is circular, and its diameter is 3 to 6 mm.

[0026] The hydrophilic-hydrophobic patterned semi-enclosed paper substrate described in step (1) is prepared by a UV curing-screen printing method, specifically by the following method:

[0027] Use a scraper to print the hydrophobic ink on the paper through a patterned screen. The ink penetrates into the paper to form a hydrophobic area, and the unpenetrated part is the detection area. It is then dried by UV light to complete the construction of the hydrophilic and hydrophobic boundary on the front side of the paper. Then turn the paper over and print the hydrophobic ink on the detection area through the screen using a scraper. The ink penetrates into the paper downward and is dried by UV light to form a patterned hydrophilic detection area with a closed bottom.

[0028] The conditions for UV light irradiation drying are: wavelength of 300nm, irradiation time of 2 to 10s.

[0029] The hydrophobic ink described in step (1) is UV light-curable ink or UV light-curable wax; preferably, it is UV light-curable transparent ink.

[0030] The paper described in step (1) is conventional paper in the art; preferably office paper, commercial filter paper or hand-made paper; more preferably double-circle qualitative filter paper 102#, Whatman 4# filter paper or hand-made paper; further preferably double-circle qualitative filter paper 102#.

[0031] The basis weight of the hand-made paper is 60-80 g / m 2 .

[0032] The volume percentage of glycerol in the glycerol aqueous solution described in step ① is 0% to 80%, preferably 20% to 40%.

[0033] The concentration of acrylamide in the acrylamide prepolymer solution described in step ① is 480-960 g / L, and the concentration of N,N-methylenebisacrylamide is 10-20 g / L.

[0034] The concentration of the gelatin prepolymer solution in step ② is 2.5-10% by mass; preferably 5-10% by mass; more preferably 5% by mass.

[0035] The volume percentage of glycerol in the glycerol aqueous solution in step ③ is 0% to 80%; preferably 60% to 80%; more preferably 60% by volume.

[0036] The concentration of the hydroxylamine hydrochloride glycerol aqueous solution in step ③ is 80-200 g / L; preferably 100-200 g / L; more preferably 100 g / L.

[0037] The volume percentage of methanol in the methanol aqueous solution described in step ④ is 0% to 60%, preferably 50% by volume.

[0038] The concentration of the methanol aqueous solution of 1,10-phenanthroline in step ④ is 25-50 g / L, preferably 25 g / L.

[0039] The hydrochloric acid aqueous solution described in step ⑤ has a pH value of 5.

[0040] The concentration of glucose oxidase in the mixed aqueous solution (detection reagent 4) described in step ⑤ is 25-50 g / L, and the concentration of horseradish catalase is 0.1-1 g / L.

[0041] The concentration of the 3,3',5,5'-tetramethylbenzidine aqueous solution in step ⑤ is 2-6 g / L, preferably 5-6 g / L, and more preferably 5 g / L.

[0042] The acrylamide prepolymer solution, the hydroxylamine hydrochloride glycerol aqueous solution and the saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution described in step ⑥ can be mixed in any volume ratio; the volume ratio is preferably 1:1:1.

[0043] The initiator described in steps ⑥ and ⑦ is at least one of ammonium persulfate (APS), potassium persulfate, azobisisobutyramidine hydrochloride (AIBA) and azobisisobutyronitrile (AIBN).

[0044] The concentration of the initiator solution in steps ⑥ and ⑦ is 5% to 20% by mass, preferably 10% by mass.

[0045] The volume ratio of the initiator solution to the acrylamide prepolymer solution in steps ⑥ and ⑦ is 1:5 to 10, preferably 1:5.

[0046] In step ⑥, the gel mixture I is added dropwise to the patterned hydrophilic detection area according to the size of the detection area; the area ratio of the gel mixture I to the detection area is about 0.26 L / m 2 (The diameter of the circular detection area is 3 to 6 mm, and the amount of gel mixture I is 5 to 30 μL).

[0047] The reaction conditions in steps ⑥ and ⑦ are: reaction at room temperature under vacuum for 1 to 4 hours; preferably: reaction at room temperature under -1 MPa vacuum for 2 hours.

[0048] The acrylamide prepolymer solution and the methanol aqueous solution of 1,10-phenanthroline described in step ⑦ can be mixed in any volume ratio; the volume ratio is preferably 1:1.

[0049] In step ⑦, the gel mixture II is added to the patterned hydrophilic detection area according to the size of the detection area; the area ratio of the gel mixture II to the detection area is about 0.26L / m 2 .

[0050] The gelatin prepolymer solution, mixed aqueous solution and 3,3',5,5'-tetramethylbenzidine aqueous solution described in step ⑧ can be mixed in any volume ratio; the volume ratio is preferably 1:1:1.

[0051] The initiator described in step ⑧ is at least one of glutaraldehyde and epichlorohydrin; preferably glutaraldehyde.

[0052] The concentration of the initiator solution in step ⑧ is 5-25% by mass, preferably 25%.

[0053] The volume ratio of the initiator solution to the gelatin prepolymer solution in step ⑧ is 1:5 to 10, preferably 1:5.

[0054] The reaction conditions described in step ⑧ are: reacting for about 30 minutes in a closed environment at room temperature.

[0055] In step ⑧, the gel mixture II is added dropwise to the patterned hydrophilic detection area according to the size of the detection area; the area ratio of the gel mixture III to the detection area is preferably 0.26 L / m 2 .

[0056] A patternable anti-"coffee ring effect" hydrogel colorimetric test paper is prepared by any of the methods described above.

[0057] The patternable anti-"coffee ring effect" hydrogel colorimetric test paper is used in detecting divalent copper ions, divalent iron ions or glucose, wherein the application is for non-disease diagnosis purposes.

[0058] A method for detecting divalent copper ions, divalent iron ions or glucose for non-disease diagnosis purposes, comprising the following steps:

[0059] (A) at least 5 standard sample solutions with concentration gradients are respectively added dropwise to the detection area of ​​the above-mentioned patternable anti-"coffee ring effect" hydrogel colorimetric test paper for reaction, dried at room temperature after the reaction, and then the color intensity of the hydrogel after the reaction is obtained by a scanner, and then a standard curve is drawn with the concentration of the standard sample solution; wherein the standard sample solution is a divalent copper ion solution, a divalent iron ion solution or a glucose solution;

[0060] (B) dropping the sample solution to be tested into the detection area of ​​the above-mentioned patternable anti-"coffee ring effect" hydrogel colorimetric test paper for reaction, drying at room temperature after the reaction, and then obtaining the color intensity of the hydrogel after the reaction by a scanner, and then obtaining the concentration (or content) of the divalent copper ion solution, divalent iron ion solution or glucose solution in the sample solution to be tested by drawing a standard curve according to step (A).

[0061] The detection temperature range is 4°C to 65°C, preferably 65°C.

[0062] The concentration of the divalent copper ion solution in step (A) is in the range of 0 to 30 ppm, preferably 0.2 to 30 ppm.

[0063] The concentration range of the divalent iron ion solution described in step (A) is 0 to 1000 μmol / L.

[0064] The concentration range of the glucose solution described in step (A) is 0 to 1000 ppm.

[0065] The reaction time in steps (A) and (B) is 10 to 30 minutes, preferably 10 minutes.

[0066] Compared with the prior art, the present invention has the following advantages and effects:

[0067] 1. The present invention provides a solution to the uneven display of colorimetric signals of paper test strips by using hydrogels. By utilizing the three-dimensional network structure of the hydrogel, the detection reagent molecules are evenly anchored in the patterned paper-based hydrogel, so that the particles to be tested can be colored "at a fixed point". Under the action of a large number of hydrophilic groups, the particles to be tested quickly penetrate into the hydrogel network with the aqueous solution, and react with the anchored detection reagent molecules to produce a color reaction, thereby avoiding the influence of capillary force and Marangoni effect, and greatly reducing the interaction between the biochemical droplets and the fiber array in the paper test strip, thereby obtaining a uniform color development result that is linearly related to the concentration of the particles to be tested.

[0068] 2. The present invention first designs two hydrogel prepolymer systems (acrylamide prepolymer and gelatin prepolymer) for different detection systems, and prepares three detection reagent systems for different analytes (a glycerol aqueous solution system composed of hydroxylamine hydrochloride and 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline is used to detect divalent copper ions; a methanol aqueous solution of 1,10-phenanthroline is used to detect divalent iron ions; an aqueous solution composed of glucose oxidase, horseradish peroxidase and 3,3',5,5'-tetramethylbenzidine is used to detect glucose), and then the detection reagent is loaded into the hydrogel three-dimensional network through a one-pot method, and further combined with the paper-based fiber array (to obtain a hydrogel paper test paper for colorimetric detection in which the hydrogel three-dimensional network and the paper-based fiber array are mutually entangled). When the sample to be detected is detected, the object to be detected reacts with the anchored detection reagent to develop color, thereby realizing uniform display of the colorimetric signal.

[0069] 3. The present invention adjusts the type of solvent added to the hydrogel (adding a water-retaining agent or an antifreeze agent such as methanol or glycerol to the hydrogel) and controls the freezing point of the detection gel in the paper test paper by adjusting the added volume fraction, so that the hydrogel can be adapted to different temperature usage ranges and has an adjustable wide operating temperature range, so that the prepared colorimetric detection hydrogel paper test paper can be detected within a wide temperature range.

[0070] 4. The present invention realizes patterned design while loading the hydrogel on the paper substrate, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 The figure is a schematic diagram of the preparation process of the copper ion paper-based hydrogel detection test paper in Example 1.

[0072] Figure 2 This is a graph showing the color response results of the copper ion paper-based hydrogel detection test paper in Example 2 under different temperature conditions.

[0073] Figure 3 It is the nasal congestion signal standard curve of the copper ion paper-based hydrogel detection test paper and the conventional copper ion detection test paper in Example 3; wherein, (a) and (c) are the colorimetric signal distribution range and linear standard curve of the conventional copper ion detection test paper, respectively; (b) and (d) are the colorimetric signal distribution range and linear standard curve of the copper ion paper-based hydrogel detection test paper of the present invention, respectively.

[0074] Figure 4 It is a comparison result diagram of the colorimetric signal uniformity of the copper ion paper-based hydrogel test paper and the conventional copper ion detection test paper in Example 4; wherein, (a), (b), (c) and (g) are respectively the actual detection color intensity effect of the conventional copper ion detection test paper, the distribution diagram of the color intensity in the radial direction (100ppm), the color intensity curve when different volumes of the test solution are added, and the color intensity three-dimensional effect diagram (100ppm); (d), (e), (f) and (h) are respectively the actual detection color intensity effect of the copper ion hydrogel test paper of the present invention, the distribution diagram of the color intensity in the radial direction (100ppm), the color intensity curve when different volumes of the test solution are added, and the color intensity three-dimensional effect diagram (100ppm).

[0075] Figure 5 The figure is a comparison result of the uniformity of the colorimetric signals of the divalent iron ion paper-based hydrogel detection test paper and the conventional iron ion detection test paper in Example 5; wherein, (a) is the colorimetric signal of the conventional test paper at different addition amounts and concentrations; (b) is the colorimetric signal of the hydrogel test paper at different concentrations; (c) is a linear graph comparing the color intensity uniformity of the conventional test paper and the hydrogel test paper (400 μM); (d) is a three-dimensional view comparison of the color intensity of the conventional test paper and the hydrogel test paper (400 μM).

[0076] Figure 6 1 is a graph comparing the uniformity of the colorimetric signals of the paper-based hydrogel test strip for glucose and the conventional glucose test strip in Example 9; wherein (a) is the colorimetric signal of the conventional test strip at different glucose concentrations; (b) is the colorimetric signal of the hydrogel test strip at different concentrations; (c) is a straight line graph comparing the color intensity uniformity of the conventional test strip and the hydrogel test strip; and (d) is a color intensity visual comparison of the conventional test strip and the hydrogel test strip (400ppm). DETAILED DESCRIPTION

[0077] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually in accordance with conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.

[0078] The pattern-customized screen printing plate involved in the embodiment of the present invention was purchased from Kaimao Technology (Shenzhen) Co., Ltd.; UV light-curing transparent ink (hereinafter referred to as UV light-curing ink) was purchased from Guangzhou Shangcai Printing Materials Co., Ltd.; double-circle qualitative filter paper 102# was purchased from Si Tuofan Technology (Hangzhou) Co., Ltd.; Whatman4# filter paper was purchased from Hangzhou Wohua Filter Paper Co., Ltd.; the hand-made paper was obtained by copying commercially available pulp board (pulp board purchased from Guangzhou Paper Mill), with a basis weight of 60-80 g / m 2 .

[0079] The preparation method of the acrylamide glycerol aqueous solution involved in the embodiment of the present invention is as follows: dissolving acrylamide in a glycerol aqueous solution (the volume fraction of glycerol in the glycerol aqueous solution is 0-80%, preferably 20-40%) to obtain an acrylamide glycerol aqueous solution.

[0080] The preparation method of the hydroxylamine hydrochloride glycerol aqueous solution involved in the embodiment of the present invention is as follows: dissolve hydroxylamine hydrochloride in a glycerol aqueous solution (the volume fraction of glycerol in the glycerol aqueous solution is 0 to 80%, preferably 40 to 80%) to obtain a hydroxylamine hydrochloride glycerol aqueous solution (concentration is 80 g / L to 200 g / L).

[0081] The preparation method of the saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution involved in the embodiment of the present invention is as follows: 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline is dissolved in methanol to prepare a saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution.

[0082] The preparation method of the methanol aqueous solution of 1,10-phenanthroline involved in the embodiment of the present invention is as follows: 1,10-phenanthroline is dissolved in a methanol aqueous solution (the volume fraction of methanol in the methanol aqueous solution is 0 to 60%) to obtain a methanol aqueous solution of 1,10-phenanthroline (concentration is 25 g / L to 50 g / L).

[0083] Example 1: Detection of divalent copper ions

[0084] (1) Preparation of hydrophilic and hydrophobic patterned semi-enclosed paper substrate: Figure 1 As shown, a circular hydrophilic pattern area with a clear hydrophilic-hydrophobic boundary and a closed bottom is printed on the double-circle qualitative filter paper 102# using pattern-customized screen printing and UV light-cured transparent ink, with a diameter of 6mm. Specifically, a hydrophobic UV light-cured ink is printed on the double-circle qualitative filter paper 102# through a patterned screen with a scraper, and the ink penetrates into the paper to form a hydrophobic area, and the unpenetrated part is the detection area. Further, under UV light irradiation, the UV light wavelength is 300nm, and the irradiation time is 10s. The ink dries and the construction of the hydrophilic-hydrophobic boundary on the front of the paper is completed; the paper is further turned over, and the UV light-cured ink is printed on the above-mentioned detection area through a scraper through a screen, and the ink infiltrates downward into the paper. After UV light irradiation, the UV light wavelength is 300nm, and the irradiation time is 2s, it is dried to form a patterned hydrophilic detection area with a closed bottom.

[0085] (2) Take 1 mL of 100 g / L hydroxylamine hydrochloride glycerol aqueous solution (the volume fraction of glycerol is 80%), 1 mL of saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution, and 1 mL of acrylamide prepolymer solution (obtained by adding the crosslinking agent N,N-methylenebisacrylamide to the acrylamide glycerol aqueous solution; wherein the mass concentration of acrylamide in the prepolymer solution is 960 g / L acrylamide, the mass concentration of N,N-methylenebisacrylamide is 20 g / L, and the volume fraction of glycerol in the acrylamide glycerol aqueous solution is 20%) and mix them evenly, then add 200 μL of 10% ammonium persulfate aqueous solution, shake evenly, and use a pipette to draw 30 μL and drop it on the circular unit detection area with a diameter of 6 mm prepared in step (1). Then transfer it to a vacuum environment with a vacuum degree of -1 MPa, react at room temperature for 2 hours, and obtain a copper ion paper-based hydrogel detection test paper. 15 μL of the prepared 10ppm divalent copper ion standard solution (copper sulfate pentahydrate, the same below) was added dropwise to the 6mm circular unit detection area filled with hydrogel, and the color intensity of the hydrogel after the reaction was obtained by a scanner (the scanner used was Epson Perfection V39 Epson scanner, the same below) after 10 minutes. Then the copper ion standard curve function was input (in the range of 0-1000ppm copper ion concentration, various copper ion standard solutions with different concentration gradients were prepared, and the color intensity of the copper ion paper-based hydrogel test paper was measured, and the curve was drawn, and the copper ion standard curve function was obtained after fitting), and the concentration of divalent copper ions was 9.3ppm.

[0086] (3) A conventional divalent copper ion colorimetric test paper is used for comparison, that is, 10 μL of 100 g / L hydroxylamine hydrochloride glycerol aqueous solution (the volume fraction of glycerol is 80%) and 10 μL of saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution are mixed and then dropped into the circular unit detection area with a diameter of 6 mm prepared in step (1), and dried to obtain a test paper that can be used for divalent copper ion detection. 15 μL of the prepared 10 ppm divalent copper ion standard solution is added dropwise to the 6 mm circular unit detection area filled with hydrogel, and the color intensity after the reaction is obtained by a scanner after drying at room temperature. Then, the copper ion standard curve function is input (the establishment of the standard curve function refers to the above step (2), and the "copper ion paper-based hydrogel detection test paper" is replaced with the "conventional divalent copper ion colorimetric detection test paper"), and the concentration of divalent copper ions is obtained to be 8.1 ppm.

[0087] Example 2: Detection of divalent copper ions

[0088] (1) Preparation of hydrophilic-hydrophobic patterned semi-enclosed paper substrate: A circular hydrophilic pattern area with a diameter of 5 mm and a clear hydrophilic-hydrophobic boundary and a closed bottom was printed on Whatman 4# filter paper using screen printing with customized patterns and UV light-curing ink. The specific preparation method was the same as in Example 1.

[0089] (2) Take 1 mL of 150 g / L hydroxylamine hydrochloride glycerol aqueous solution (the volume fraction of glycerol is 60%), 1 mL of saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution, and 1 mL of acrylamide prepolymer solution (obtained by adding the crosslinking agent N,N-methylenebisacrylamide to the acrylamide glycerol aqueous solution; wherein the mass concentration of acrylamide in the prepolymer solution is 480 g / L, the mass concentration of N,N-methylenebisacrylamide is 10 g / L, and the volume fraction of glycerol in the acrylamide glycerol aqueous solution is 40%) and mix them evenly, then add 200 μL of 8% ammonium persulfate aqueous solution, shake evenly, and use a pipette to draw 21 μL and drop it on the circular unit detection area with a diameter of 5 mm prepared in step (1). Then transfer it to a vacuum environment (-1 MPa) and react at room temperature for 2 hours to obtain a copper ion paper-based hydrogel detection test paper. 10 μL of the prepared 10 ppm divalent copper ion standard solution was added dropwise to the 5 mm circular unit detection area filled with hydrogel, and the color intensity of the hydrogel after the reaction was obtained by a scanner after 10 minutes. Then, the copper ion standard curve function was input (the method for obtaining the standard curve function was the same as step (2) of Example 1), and the concentration of divalent copper ions was obtained to be 9.5 ppm.

[0090] (3) Using conventional divalent copper ion colorimetric test paper for comparison, 7 μL of 100 g / L hydroxylamine hydrochloride glycerol aqueous solution (the volume fraction of glycerol is 60%) and 7 μL of saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution were mixed and then added dropwise to the circular unit detection area with a diameter of 5 mm prepared in step (1), and dried to obtain a test paper that can be used for divalent copper ion detection. 7 μL of the prepared 10 ppm divalent copper ion standard solution was added dropwise to the 5 mm circular unit detection area filled with hydrogel, and the color intensity after the reaction was obtained by a scanner after drying at room temperature. Then the copper ion standard curve function was input (the method for obtaining the standard curve function was the same as step (3) of Example 1), and the concentration of divalent copper ions was obtained to be 8.6 ppm.

[0091] (4) The copper ion paper-based hydrogel test paper prepared in step (2) was further directly placed at -20°C, 4°C, 25°C and 65°C for testing, and its colorimetric response under different temperature environments was tested using a scanner. The results are as follows: Figure 2As shown, the paper-based hydrogel can still achieve uniform colorimetric detection and presentation from 4°C to 65°C. The color intensity at high temperature is stronger than that at room temperature, and it has higher sensitivity.

[0092] Example 3: Detection of divalent copper ions

[0093] (1) Preparation of hydrophilic / hydrophobic patterned semi-enclosed paper substrate: Using screen printing and UV light-curing ink with customized patterns, the substrate was prepared at 80 g / m 2 The hand-made paper is printed with a circular hydrophilic pattern area having a clear hydrophilic-hydrophobic boundary and a closed bottom, with a diameter of 4 mm. The specific preparation method is the same as that of Example 1.

[0094] (2) Take 1 mL of 200 g / L hydroxylamine hydrochloride glycerol aqueous solution (the volume fraction of glycerol is 60%), 1 mL of saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution, and 1 mL of acrylamide prepolymer solution (obtained by adding the crosslinking agent N,N-methylenebisacrylamide to the acrylamide glycerol aqueous solution; wherein the mass concentration of acrylamide in the prepolymer solution is 480 g / L, the mass concentration of N,N-methylenebisacrylamide is 10 g / L, and the volume fraction of glycerol in the acrylamide glycerol aqueous solution is 40%) and mix them evenly, then add 200 μL of 15% azobisisobutyronitrile aqueous solution, shake evenly, and use a pipette to draw 13.3 μL and drop it on the circular unit detection area with a diameter of 4 mm prepared in step (1). Then transfer it to a vacuum environment (-1 MPa) and react at room temperature for 2 hours to obtain a copper ion paper-based hydrogel detection test paper. 4.3 μL of the prepared 10 ppm divalent copper ion standard solution was added dropwise to the 4 mm circular unit detection area filled with hydrogel. After 10 minutes, the color intensity of the hydrogel after the reaction was obtained by scanning. Then, the copper ion standard curve function was input (the method for obtaining the standard curve function was the same as step (2) of Example 1), as shown in FIG. Figure 3 As shown in (b) and 3(d), the concentration of divalent copper ions was 9.8 ppm.

[0095] (3) Using conventional divalent copper ion colorimetric test paper for comparison, 4.3 μL of 100 g / L hydroxylamine hydrochloride glycerol aqueous solution (the volume fraction of glycerol is 60%) and 4.3 μL of saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution were mixed and then dropped into the circular unit detection area with a diameter of 4 mm prepared in step (1). After drying, a test paper that can be used for divalent copper ion detection was obtained. 4.3 μL of the prepared 10 ppm divalent copper ion standard solution was aspirated and dropped into the 4 mm circular unit detection area filled with hydrogel. After drying at room temperature, the color intensity after the reaction was obtained by a scanner. Then, the copper ion standard curve function was input (the method for obtaining the standard curve function was the same as step (3) of Example 1), as shown in FIG. Figure 3As shown in Figures 3(a) and 3(c), the concentration of divalent copper ions was calculated to be 9.2 ppm.

[0096] Example 4: Detection of divalent copper ions

[0097] (1) Preparation of hydrophilic-hydrophobic patterned semi-enclosed paper substrate: Using screen printing with customized patterns and UV light-curing ink, a circular hydrophilic pattern area with a clear hydrophilic-hydrophobic boundary and a closed bottom was printed on double-circle qualitative filter paper 102#, with a diameter of 3 mm. The specific preparation method is the same as in Example 1.

[0098] (2) Take 1 mL of 100 g / L hydroxylamine hydrochloride glycerol aqueous solution (the volume fraction of glycerol is 60%), 1 mL of saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution, and 1 mL of acrylamide prepolymer solution (obtained by adding the crosslinking agent N,N-methylenebisacrylamide to the acrylamide glycerol aqueous solution; wherein the mass concentration of acrylamide in the prepolymer solution is 960 g / L, the mass concentration of N,N-methylenebisacrylamide is 20 g / L, and the volume fraction of glycerol in the acrylamide glycerol aqueous solution is 40%) and mix them evenly, then add 100 μL of 20% potassium persulfate aqueous solution, shake evenly, and use a pipette to draw 7.5 μL and drop it on the circular unit detection area with a diameter of 3 mm prepared in step (1). Then transfer it to a vacuum environment (-1 MPa) and react at room temperature for 2 hours to obtain a copper ion paper-based hydrogel detection test paper. 2.5 μL of the prepared 10 ppm divalent copper ion standard solution was added dropwise to the 3 mm circular unit detection area filled with hydrogel, and the color intensity of the hydrogel after the reaction was obtained by a scanner after 10 minutes. Then, the copper ion standard curve function was input (the method for obtaining the standard curve function was the same as step (2) of Example 1), and the concentration of divalent copper ions was obtained to be 9.9 ppm.

[0099] (3) Using conventional divalent copper ion colorimetric test paper for comparison, 2.5 μL of 100 g / L hydroxylamine hydrochloride glycerol aqueous solution (the volume fraction of glycerol is 60%) and 2.5 μL of saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution were mixed and then added dropwise to the circular unit detection area with a diameter of 3 mm prepared in step (1), and dried to obtain a test paper that can be used for divalent copper ion detection. 2.5 μL of the prepared 10 ppm divalent copper ion standard solution was added dropwise to the 3 mm circular unit detection area filled with hydrogel, dried at room temperature, and the color intensity after the reaction was obtained by a scanner, and then the copper ion standard curve function was input (the method for obtaining the standard curve function was the same as step (3) of Example 1), and the concentration of divalent copper ions was obtained to be 9.2 ppm.

[0100] (4) The uniformity of the colorimetric signal in the circular detection area of ​​the conventional divalent copper ion colorimetric detection paper and the copper ion paper-based hydrogel detection paper of the present invention was further compared by ImageJ: different volumes (5, 10, 15, 20 μL) of divalent copper ion standard solution (concentration of 1, 5, 10, 20, 50, 100 ppm) were respectively added dropwise to the circular unit detection area with a diameter of 3 mm prepared in the above step (1), and the detection effects of the two detection papers were compared.

[0101] Test results such as Figure 4 As shown: the conventional divalent copper ion colorimetric test paper shows an obvious "coffee ring effect" (see Figure 4 (a)), while the copper ion paper-based hydrogel test paper of the present invention achieves uniform color development at all test solution concentrations and addition amounts (see Figure 4 (d)); Figure 4 As shown in (b) and 4 (e), in terms of the fluctuation range of radial color grayscale, the noise of the color intensity of the copper ion paper-based hydrogel detection test paper of the present invention is significantly smaller than that of the conventional paper test paper, which is consistent with Figure 4 The three-dimensional distribution results of color intensity in (g) and 4(h) are consistent; and Figure 4 As shown in (c) and 4(f), under the same addition volume conditions, the color intensity of the copper ion paper-based hydrogel detection paper in the present invention is greater than that of the conventional divalent copper ion colorimetric detection paper. At the same time, the detection limit of the conventional divalent copper ion colorimetric detection paper is 1ppm, and the linear range is 1-10ppm, while the detection limit of the copper ion paper-based hydrogel detection paper in the present invention is 0.1ppm, and the linear range is 0.2-30ppm, which has higher sensitivity and linear range.

[0102] Example 5: Detection of ferrous ions

[0103] (1) Preparation of hydrophilic-hydrophobic patterned semi-enclosed paper substrate: Using screen printing with customized patterns and UV light-curing ink, a circular hydrophilic pattern area with a clear hydrophilic-hydrophobic boundary and a closed bottom was printed on double-circle qualitative filter paper 102#, with a diameter of 3 mm. The specific preparation method is the same as in Example 1.

[0104] (2) 1 mL of 25 g / L 1,10-phenanthroline methanol aqueous solution (methanol volume fraction of 50%) and 1 mL of acrylamide prepolymer solution (obtained by adding crosslinking agent N,N-methylenebisacrylamide to acrylamide glycerol aqueous solution; wherein the mass concentration of acrylamide in the prepolymer solution is 480 g / L, the mass concentration of N,N-methylenebisacrylamide is 10 g / L, and the volume fraction of glycerol in the acrylamide glycerol aqueous solution is 40%) are mixed evenly, and then 200 μL of 10% ammonium persulfate aqueous solution is added, and after shaking evenly, 7.5 μL is taken with a pipette and dropped into the circular unit detection area with a diameter of 3 mm prepared in step (1). Then, it is transferred to a vacuum environment (-1 MPa) and reacted at room temperature for 2 hours to obtain an iron ion paper-based hydrogel detection test paper. 2.5 μL of 100 μM ferrous iron (ferrous chloride, the same below) standard solution was added to the 3 mm circular unit detection area filled with hydrogel. After 10 minutes, the color intensity of the hydrogel after the reaction was obtained by scanning. Then the iron ion standard curve function was input (in the range of 0-5000 μM ferrous iron concentration, various ferrous iron standard solutions with different concentration gradients were prepared, and the color intensity of the ferrous paper-based hydrogel test paper was measured, and the curve was drawn. After fitting, the ferrous iron standard curve function was obtained, and the concentration of ferrous iron was 100.2 μM.

[0105] (3) Using conventional ferrous ion colorimetric test paper as a comparison, 5 μL of 1,10-phenanthroline methanol aqueous solution (methanol volume fraction of 60%) with a mass concentration of 25 g / L was added dropwise to the circular unit detection area with a diameter of 3 mm prepared in step (1), and dried to obtain a conventional test paper that can be used for ferrous ion detection. 2.5 μL of the prepared 100 μM ferrous ion standard solution was added dropwise to the 3 mm circular unit detection area filled with hydrogel, and the color intensity after the reaction was obtained by a scanner after drying at room temperature. Then, the iron ion standard curve function was input (the establishment of the standard curve function refers to the above step (2), and the "iron ion paper-based hydrogel detection test paper" was replaced with the "conventional ferrous ion colorimetric detection paper test paper"), and the concentration of ferrous ions was obtained to be 90.3 μM.

[0106] (4) The uniformity of the colorimetric signal in the circular detection area of ​​the conventional divalent iron ion colorimetric detection paper and the iron ion paper-based hydrogel detection paper of the present invention was further compared by ImageJ: different volumes (1, 2, 3, 4 μL) of divalent iron ion standard solution (concentration of 0, 20, 50, 100, 200, 400, 1000 μM) were respectively added dropwise to the circular unit detection area with a diameter of 3 mm prepared in the above step (1), and the detection effects of the two detection papers were compared.

[0107] result Figure 5As shown: the conventional ferrous ion colorimetric test paper shows an obvious "coffee ring effect" (see Figure 5 (a)), while the iron ion paper-based hydrogel test paper of the present invention can maintain uniform color development (see Figure 5 (b)); Figure 5 As shown in (c), in terms of the fluctuation range of radial color grayscale of the two, the noise of the color intensity of the iron ion paper-based hydrogel detection test paper in the present invention is significantly smaller than that of the conventional divalent iron ion colorimetric detection test paper, which is consistent with Figure 5 The three-dimensional distribution results of the respective color intensities in (d) are consistent.

[0108] Example 6: Detection of ferrous ions

[0109] (1) Preparation of hydrophilic-hydrophobic patterned semi-enclosed paper substrate: A circular hydrophilic pattern area with a diameter of 5 mm and a clear hydrophilic-hydrophobic boundary and a closed bottom was printed on Whatman 4# filter paper using screen printing with customized patterns and UV light-curing ink. The specific preparation method was the same as in Example 1.

[0110] (2) 1 mL of 50 g / L 1,10-phenanthroline methanol aqueous solution (methanol volume fraction of 40%) and 1 mL of acrylamide prepolymer solution (obtained by adding crosslinking agent N,N-methylenebisacrylamide to acrylamide glycerol aqueous solution; wherein the mass concentration of acrylamide in the prepolymer solution is 480 g / L, the mass concentration of N,N-methylenebisacrylamide is 10 g / L, and the volume fraction of glycerol in the acrylamide glycerol aqueous solution is 60%) are mixed evenly, and then 400 μL of 5% ammonium persulfate aqueous solution is added, and after shaking evenly, 21 μL is taken with a pipette and dropped into the circular unit detection area with a diameter of 5 mm prepared in step (1). Then, it is transferred to a vacuum environment (-1 MPa) and reacted at room temperature for 2 hours to obtain an iron ion paper-based hydrogel detection test paper. 7 μL of a 100 μM ferrous iron standard solution was added dropwise to the 5 mm circular unit detection area filled with hydrogel, and the color intensity of the hydrogel after the reaction was obtained by a scanner after 10 minutes. Then, the ferrous iron standard curve function was input (the method for obtaining the standard curve function was the same as step (2) of Example 5), and the concentration of ferrous iron was obtained to be 99.6 μM.

[0111] (3) Using conventional ferrous ion colorimetric test paper as a comparison, 14 μL of a 25 g / L 1,10-phenanthroline methanol aqueous solution (methanol volume fraction of 30%) was added dropwise to the circular unit detection area with a diameter of 5 mm prepared in step (1), and dried to obtain a test paper that can be used for ferrous ion detection. 7 μL of a 100 μM ferrous ion standard solution was added dropwise to a 3 mm circular unit detection area filled with hydrogel, and the color intensity after the reaction was obtained by a scanner after drying at room temperature. Then, the ferrous ion standard curve function was input (the method for obtaining the standard curve function was the same as that of step (3) of Example 5), and the concentration of ferrous ions was obtained to be 94.4 μM.

[0112] Example 7: Detection of ferrous ions

[0113] (1) Preparation of hydrophilic-hydrophobic patterned semi-enclosed paper substrate: Using screen printing with customized patterns and UV light-curing ink, a circular hydrophilic pattern area with a diameter of 4 mm and a closed bottom with a clear hydrophilic-hydrophobic boundary was printed on hand-made paper. The specific preparation method was the same as in Example 1.

[0114] (2) 1 mL of 50 g / L 1,10-phenanthroline methanol aqueous solution (methanol volume fraction is 0%) and 1 mL of acrylamide prepolymer solution (obtained by adding crosslinking agent N,N-methylenebisacrylamide to acrylamide glycerol aqueous solution; wherein the mass concentration of acrylamide in the prepolymer solution is 960 g / L, the mass concentration of N,N-methylenebisacrylamide is 20 g / L, and the volume fraction of glycerol in the acrylamide glycerol aqueous solution is 60%) are mixed evenly, and then 100 μL of 20% azobisisobutylamidine hydrochloride aqueous solution is added, and after shaking evenly, 13.3 μL is taken with a pipette and dropped into the circular unit detection area with a diameter of 4 mm prepared in step (1). Then, it is transferred to a vacuum environment (-1 MPa) and reacted at room temperature for 2 hours to obtain an iron ion paper-based hydrogel detection test paper. 4.3 μL of 100 μM ferrous iron standard solution was added dropwise to the 4 mm circular unit detection area filled with hydrogel, and the color intensity of the hydrogel after the reaction was obtained by scanning after 10 minutes. Then, the ferrous iron standard curve function was input (the method for obtaining the standard curve function was the same as step (2) of Example 5), and the concentration of ferrous iron was obtained to be 99.2 μM.

[0115] (3) Using conventional ferrous ion colorimetric test paper for comparison, 8.6 μL of 25 g / L 1,10-phenanthroline methanol aqueous solution (methanol volume fraction is 0%) was added dropwise to the circular unit detection area with a diameter of 4 mm prepared in step (1), and dried to obtain a test paper that can be used for ferrous ion detection. 4.3 μL of the test solution was added dropwise to the 4 mm circular unit detection area filled with hydrogel, and after drying at room temperature, the color intensity after the reaction was obtained by a scanner, and then the ferrous ion standard curve function was input (the standard curve function was obtained in the same way as in step (3) of Example 5), and the concentration of ferrous ions was obtained to be 89.7 μM.

[0116] Example 8: Detection of Glucose

[0117] (1) Preparation of hydrophilic-hydrophobic patterned semi-enclosed paper substrate: Using screen printing with customized patterns and UV light-curing ink, a circular hydrophilic pattern area with a diameter of 4 mm with a clear hydrophilic-hydrophobic boundary and a closed bottom was printed on double-circle qualitative filter paper 102#. The specific preparation method is the same as in Example 1.

[0118] (2) 1 mL of a mixed aqueous solution of 25 g / L glucose oxidase and 0.1 g / L horseradish peroxidase (solvent is a hydrochloric acid aqueous solution with a pH of 5), 1 mL of a 5 g / L 3,3',5,5'-tetramethylbenzidine aqueous solution, and 1 mL of a 5% gelatin aqueous solution (gelatin prepolymer solution) were mixed, and 200 μL of a 25% glutaraldehyde aqueous solution was added. After shaking evenly, 15 μL was pipetted with a pipette and dropped into the circular unit detection area with a diameter of 4 mm prepared in step (1). After reacting for 30 minutes in a closed environment at room temperature, a paper-based hydrogel test strip for detecting glucose was obtained. 4.3 μL of a 100 ppm glucose standard solution was pipetted and dropped into the 4 mm circular unit detection area filled with hydrogel. After 10 minutes, the color intensity of the hydrogel after the reaction was obtained by a scanner. Then, the glucose standard curve function was input (in the glucose concentration range of 0 to 6000 ppm, various glucose standard solutions with different concentration gradients were prepared, their color intensity on the paper-based hydrogel test strip was measured, the curve was drawn, and the glucose standard curve function was obtained after fitting), and the glucose concentration was obtained to be 100.6 ppm.

[0119] (3) For comparison with conventional glucose test strips, 4.3 μL of an aqueous solution of 25 g / L glucose oxidase and 0.1 g / L horseradish peroxidase (solvent is a hydrochloric acid aqueous solution with a pH of 5) and 4.3 μL of a 5 g / L 3,3',5,5'-tetramethylbenzidine aqueous solution were mixed evenly, and 5 μL of the mixture was dripped into the circular unit detection area with a diameter of 4 mm prepared in step (1). After drying, a test strip that can be used to detect glucose was obtained. 4.3 μL of a prepared 100 ppm glucose standard solution was dripped into the 4 mm circular unit detection area filled with hydrogel, and after drying at room temperature, the color intensity after the reaction was obtained by a scanner, and then the glucose standard curve function was input (the establishment of the standard curve function refers to the above step (2), and "paper-based hydrogel test strip for detecting glucose" is replaced with "conventional glucose test strip"), and the glucose concentration was obtained to be 99.1 ppm.

[0120] (4) The uniformity of the colorimetric signal in the circular detection area of ​​the conventional glucose test strip and the paper-based hydrogel test strip for detecting glucose of the present invention was further compared by ImageJ: different volumes (1.5 μL, 3 μL, 4.3 μL) of glucose standard solution (concentrations of 0, 50, 100, 200, 400, 1000 ppm) were respectively added dropwise to the circular unit detection area with a diameter of 3 mm prepared in the above step (1), and the detection effects of the two test strips were compared.

[0121] The results are as follows Figure 6 As shown: Conventional test paper shows obvious "coffee ring effect" (see Figure 6 (a)), the paper-based hydrogel test paper for detecting glucose in the present invention can maintain uniform color development (see Figure 6 (b)); Figure 6 As shown in (c), in terms of the fluctuation range of radial color grayscale, the noise of the color intensity of the paper-based hydrogel in the present invention is significantly smaller than that of the conventional test paper, which is consistent with Figure 6 The three-dimensional distribution results of the respective color intensities in (d) are consistent.

[0122] Example 9: Detection of Glucose

[0123] (1) Preparation of hydrophilic-hydrophobic patterned semi-enclosed paper substrate: Using screen printing with customized patterns and UV light-curing ink, a circular hydrophilic pattern area with a clear hydrophilic-hydrophobic boundary and a closed bottom was printed on hand-made paper with a diameter of 3 mm. The specific preparation method was the same as in Example 1.

[0124] (2) 1 mL of a mixed aqueous solution of 50 g / L glucose oxidase and 1 g / L horseradish peroxidase (solvent is a hydrochloric acid aqueous solution with a pH of 5), 1 mL of a 6 g / L 3,3',5,5'-tetramethylbenzidine aqueous solution, and 1 mL of a 10% gelatin aqueous solution were mixed, and 200 μL of a 25% glutaraldehyde aqueous solution was added. After shaking evenly, 7.5 μL was pipetted with a pipette and dropped into the circular unit detection area with a diameter of 3 mm prepared in step (1). After reacting for 30 minutes in a closed environment at room temperature, a hydrogel test strip for detecting glucose was obtained. 2.5 μL of a 100 ppm glucose standard solution was added dropwise to the 3 mm circular unit detection area filled with hydrogel. After 10 minutes, the color intensity of the hydrogel after the reaction was obtained by a scanner. Then, the glucose standard curve function was input (the method for obtaining the standard curve function was the same as that of step (2) in Example 8), and the glucose concentration was obtained to be 99.8 ppm.

[0125] (3) Using conventional glucose test strips as a comparison, 2.5 μL of a mixed aqueous solution of 25 g / L glucose oxidase and 1 g / L horseradish peroxidase (solvent is a hydrochloric acid aqueous solution with a pH of 5) and 2.5 μL of a 6 g / L 3,3',5,5'-tetramethylbenzidine aqueous solution were mixed evenly, and 5 μL of the mixed solution was dripped into the circular unit detection area with a diameter of 3 mm prepared in step (1). After drying, a test strip that can be used to detect glucose was obtained. 2.5 μL of a prepared 100 ppm glucose standard solution was dripped into the 3 mm circular unit detection area filled with hydrogel, and after drying at room temperature, the color intensity after the reaction was obtained by a scanner, and then the glucose standard curve function was input (the method for obtaining the standard curve function was the same as step (3) of Example 8), and the glucose concentration was obtained to be 98.4 ppm.

[0126] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a patternable anti-"coffee ring effect" hydrogel colorimetric test paper, characterized in that: The steps include: (1) Preparation of hydrophilic and hydrophobic patterned semi-enclosed paper substrate: A hydrophilic pattern area with a hydrophilic-hydrophobic boundary and a closed bottom is printed on paper by screen printing and ink, and a patterned hydrophilic detection area is obtained after UV curing; (2) Preparation of hydrogel prepolymer solution ① Acrylamide prepolymer solution: dissolve acrylamide in glycerol aqueous solution, add cross-linking agent N,N-methylenebisacrylamide, stir until clear and transparent to obtain acrylamide prepolymer solution; ② Gelatin prepolymer solution: dissolve gelatin in water to obtain gelatin prepolymer solution; (3) Preparation of detection reagents ③ Preparation of copper ion detection reagent: dissolve hydroxylamine hydrochloride in glycerol aqueous solution to obtain hydroxylamine hydrochloride glycerol aqueous solution; dissolve 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline in methanol to prepare a saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution; ④ Preparation of divalent iron ion detection reagent: dissolve 1,10-phenanthroline in methanol aqueous solution to obtain a methanol aqueous solution of 1,10-phenanthroline; ⑤ Preparation of glucose detection reagent: dissolve glucose oxidase and horseradish peroxidase in hydrochloric acid aqueous solution to obtain a mixed aqueous solution; dissolve 3,3',5,5'-tetramethylbenzidine in water to obtain a 3,3',5,5'-tetramethylbenzidine aqueous solution; (4) Preparation of paper-based colorimetric detection hydrogel ⑥ Copper ion colorimetric detection hydrogel test paper: the acrylamide prepolymer solution obtained in step ①, the hydroxylamine hydrochloride glycerol aqueous solution obtained in step ③ and the saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution are mixed evenly, and then the initiator solution is added and shaken to mix evenly to obtain a gel mixture I; the gel mixture I is then added dropwise to the patterned hydrophilic detection area obtained in step (1), and then transferred to a vacuum environment for reaction to obtain a copper ion colorimetric detection hydrogel test paper, that is, the patternable anti-"coffee ring effect" hydrogel colorimetric detection test paper; ⑦ Hydrogel test paper for colorimetric detection of divalent iron ions: the acrylamide prepolymer solution obtained in step ① and the methanol aqueous solution of 1,10-phenanthroline obtained in step ④ are mixed evenly, and then the initiator solution is added and shaken to mix evenly to obtain a gel mixture II; the gel mixture II is then added dropwise to the patterned hydrophilic detection area obtained in step (1), and then transferred to a vacuum environment for reaction to obtain a hydrogel test paper for colorimetric detection of divalent iron ions, i.e., the patternable anti-"coffee ring effect" hydrogel colorimetric detection test paper; ⑧ Glucose colorimetric detection hydrogel test paper: the gelatin prepolymer solution obtained in step ②, the mixed aqueous solution obtained in step ⑤ and the 3,3',5,5'-tetramethylbenzidine aqueous solution are mixed evenly, and then the initiator solution is added and shaken to mix evenly to obtain a gel mixture III; the gel mixture III is then added dropwise to the patterned hydrophilic detection area obtained in step (1), and then transferred to a closed environment at room temperature for reaction to obtain a glucose colorimetric detection hydrogel test paper, that is, the patternable anti-"coffee ring effect" hydrogel colorimetric detection test paper.

2. The preparation method according to claim 1, characterized in that: The hydrophilic-hydrophobic patterned semi-enclosed paper substrate described in step (1) is prepared by a UV curing-screen printing method, and the specific process is as follows: Use a scraper to print the hydrophobic ink on the paper through a patterned screen. The ink penetrates into the paper to form a hydrophobic area, and the unpenetrated part is the detection area. Then it is dried by UV light to complete the construction of the hydrophilic and hydrophobic boundary on the front side of the paper. Then turn the paper over, and use a scraper to print the hydrophobic ink on the detection area through the screen. The ink will penetrate into the paper downwards, and after drying under UV light, a patterned hydrophilic detection area with a closed bottom will be formed. The conditions for UV light irradiation drying are: wavelength of 300nm, irradiation time of 2 to 10s.

3. The preparation method according to claim 1, characterized in that: The volume percentage of glycerol in the glycerol aqueous solution described in step ① is 0% to 80%; The concentration of acrylamide in the acrylamide prepolymer solution described in step ① is 480-960 g / L, and the concentration of N,N-methylenebisacrylamide is 10-20 g / L; The concentration of the gelatin prepolymer solution in step ② is 2.5-10% by mass; The volume percentage of glycerol in the glycerol aqueous solution described in step ③ is 0% to 80%; The concentration of the hydroxylamine hydrochloride glycerol aqueous solution described in step ③ is 80-200 g / L; The volume percentage of methanol in the methanol aqueous solution described in step ④ is 0% to 60%; The concentration of the methanol aqueous solution of 1,10-phenanthroline described in step ④ is 25-50 g / L; The hydrochloric acid aqueous solution described in step ⑤ has a pH of 5; The concentration of glucose oxidase in the mixed aqueous solution in step ⑤ is 25-50 g / L, and the concentration of horseradish catalase is 0.1-1 g / L; The concentration of the 3,3',5,5'-tetramethylbenzidine aqueous solution in step ⑤ is 2 to 6 g / L; The product ratio of the acrylamide prepolymer solution, the hydroxylamine hydrochloride glycerol aqueous solution and the saturated 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline methanol solution described in step ⑥ is 1:1:1; The volume ratio of the acrylamide prepolymer solution and the methanol aqueous solution of 1,10-phenanthroline described in step ⑦ is 1:1; The volume ratio of the gelatin prepolymer solution, the mixed aqueous solution and the 3,3',5,5'-tetramethylbenzidine aqueous solution described in step ⑧ is 1:1:

1.

4. The preparation method according to claim 3, characterized in that: The volume percentage of glycerol in the glycerol aqueous solution described in step ① is 20% to 40%; The concentration of the gelatin prepolymer solution in step ② is 5-10% by mass; The volume percentage of glycerol in the glycerol aqueous solution described in step ③ is 60% to 80%; The concentration of the hydroxylamine hydrochloride glycerol aqueous solution described in step ③ is 100-200 g / L; The volume percentage of methanol in the methanol aqueous solution described in step ④ is 50%; The concentration of the methanol aqueous solution of 1,10-phenanthroline described in step ④ is 25 g / L; The concentration of the 3,3',5,5'-tetramethylbenzidine aqueous solution in step ⑤ is 5-6 g / L.

5. The preparation method according to claim 1, characterized in that: The initiator in steps ⑥ and ⑦ is at least one of ammonium persulfate, potassium persulfate, azobisisobutyramidine hydrochloride and azobisisobutyronitrile; The concentration of the initiator solution in steps ⑥ and ⑦ is 5% to 20% by mass; The volume ratio of the initiator solution to the acrylamide prepolymer solution in steps ⑥ and ⑦ is 1:5-10; The initiator in step ⑧ is at least one of glutaraldehyde and epichlorohydrin; The concentration of the initiator solution in step ⑧ is 5 to 25% by mass; The volume ratio of the initiator solution to the gelatin prepolymer solution described in step ⑧ is 1:5-10.

6. The preparation method according to claim 1, characterized in that: The hydrophobic ink described in step (1) is UV light curing ink or UV light curing wax; The paper in step (1) is office paper, commercial filter paper or hand-made paper; The patterned hydrophilic detection area described in step (1) is a circular patterned hydrophilic detection area with a diameter of 2 to 6 mm; The reaction conditions in steps ⑥ and ⑦ are: reacting at room temperature under vacuum for 1 to 4 hours; The reaction conditions described in step ⑧ are: reaction at room temperature in a closed environment for 30 minutes.

7. A patternable anti-"coffee ring effect" hydrogel colorimetric test paper, characterized in that: It is prepared by the method according to any one of claims 1 to 6.

8. The use of the patternable anti-"coffee ring effect" hydrogel colorimetric test paper according to claim 7 in detecting divalent copper ions, divalent iron ions or glucose, characterized in that: The application is for non-disease diagnosis purposes.

9. A method for detecting divalent copper ions, divalent iron ions or glucose for non-disease diagnosis purposes, characterized in that: The steps include: (A) at least 5 standard sample solutions with concentration gradients are respectively added dropwise to the detection area of ​​the patternable anti-"coffee ring effect" hydrogel colorimetric test paper of claim 7 for reaction, dried at room temperature after the reaction, and then the color intensity of the hydrogel after the reaction is obtained by a scanner, and then a standard curve is drawn with the concentration of the standard sample solution; wherein the standard sample solution is a divalent copper ion solution, a divalent iron ion solution or a glucose solution; (B) dropping the sample solution to be tested into the detection area of ​​the patternable anti-"coffee ring effect" hydrogel colorimetric test paper of claim 7 for reaction, drying at room temperature after the reaction, and then obtaining the color intensity of the hydrogel after the reaction by a scanner, and then obtaining the concentration of the divalent copper ion solution, the divalent iron ion solution or the glucose solution in the sample solution to be tested according to the standard curve drawn in step (A); The temperature range of the detection is 4°C to 65°C.

10. The method according to claim 9, characterized in that: The temperature range of the detection is 65°C; The reaction time in steps (A) and (B) is 10 to 30 minutes.

Citation Information

Patent Citations

  • Colorimetric gel for quickly detecting non-system explosive raw material urea and preparation method thereof

    CN109870417A

  • Chip colorimetric detection method based on light transmission result analysis

    CN110672594A